Frasa Preposisional Bermakna Tempat dalam Kalimat Bahasa Bugis: Suatu Kajian Struktur dan Sematik - Haedariah, Haedariah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
The research entitled "Prepositional Phrases Meaningful Places in Bugis Sentences" describe prepositions in Bugis in terms of form, meaning and category. The method used in this research is descriptive distribution. The main data of this research comes from written language, while the oral and artificial data are used as supporting data. The research aims to (1) describe the prepositions of the meaning of places in Buginese, (2) describe the linguistic elements associated with Bugis language prepositions, (3) describe the functions occupied by prepositional phrases meaning place in Bugis language, and (4) describe the meaning the place contained in the prepositions in the Buginese language. The results of this study. Keywords: Prasa, Preposition, Linguistic Elements, Syntax Function